IMPLEMENTASI NEAREST NEIGHBOR METHODS DAN CLOSED INSERTION METHODS PADA PENENTUAN RUTE BUS TRANS METRO DELI MENUJU PUSAT KOTA MEDAN - Yuniar, Nana; Panjaitan, Dedy Juliandri (LPPM Universitas Bina Bangsa, 2024)
One of the factors causing traffic jams is the use of too many private vehicles. The government is making efforts by introducing the Trans Metro Deli Bus to make it easier for people to travel, especially to the center of Medan City. However, people do not know the effective route to take to minimize the distance and time traveled. The aim of this research is to compile the Deli Trans Metro Bus route into a graph and determine the fastest route between the two routes, namely the Amplas - Merdeka Field route and the Tembung - Merdeka Field route. The data used is travel route data and distances between Trans Metro Deli Bus stops. The methods used are nearest neighbor methods and closed insertion methods. The research results obtained are that the two Trans Metro Deli Bus routes can be represented in graphs, then the Amplas - Merdeka Square route is effectively faster to the center of Medan City with a distance of 18.62 km compared to the Tembung - Merdeka Square route. The results of this research will make it easier for people who want to take a faster route to the center of Medan City.